Digteren Goldschmidt og Grundtvig - Bredsdorff, Morten (Grundtvig-Studier, 1974)
Goldschmidt and Grundtvig. A showdown concerning national identity By Morten Bredsdorff It is a well-known fact that the sarcasms of the political pamphlet »The Corsair« written by its editor M. A. Goldschmidt the journalist and poet had an immense influence on Søren Kierkegaard the philosopher. Not so with Grundtvig. Goldschmidt at that time had little interest in Grundtvig and confined himself to more or less innocent jokes concerning the comical aspects of Grundtvig’s archaic language and queer Nordic ideas. But during the war with Schleswig-Holstein, 1848-50, there was a bitter clash between the internationally-orientated Jewish author and the herald of indigenous Danish culture. Their discussion, which is of far reaching interest, may be followed in Goldschmidt’s monthly »North and South« and in Grundtvig’s newborn paper »The Dane«. After having given up »The Corsair« in 1843 Goldschmidt went abroad and studied political and economic conditions in Germany, Austria, Italy and Switzerland during the revolutionary 1840s. He was especially impressed by the political situation in the Alpine republic, where a transformation of a mediaeval, rather loose union of small societies into a confederation of cantons was taking place. It struck Goldschmidt that a similar solution of national problems within the Danish-German Monarchy might be possible, if the Danish government gave the inhabitants of Holstein and Schleswig political freedom and Parliamentarian institutions. This might in a healthy way pave the way for democracy in the whole country, thus preventing the imminent danger of internal strife and warfare. Six years later in 1853 Goldschmidt left the political life of his country with a bitter confession: »Nothing has been so devastating to me as what I learnt in Switzerland. Without this experience I might never have observed that within the Danish Monarchy there were two nations, which might, following the Swiss example, have been united in a federal state, growing healthy and strong by means of communal institutions. - For this Mr. Grundtvig excommunicated me, and the rest of them scolded me, indeed, what didn’t they do! This is the reason why I never succeeded in Denmark!« During the period leading up to the revolt in Schleswig-Holstein and even after the beginning of the war Goldschmidt used his monthly journal to advocate plans for keeping the monarchy with its two languages together by means of a political and democratic federation. He was met by bitter opposition from the ruling National-Liberal Party, which advocated the secession of Holstein and a forced unification of Schleswig with Denmark. This Goldschmidt found absolutely unjustified. And for a short time he nourished the hope of being understood by Grundtvig who scorned the »NationalLiberal gentlemen« and wanted to know the opinion of the population of Schleswig, probably having a sort of plebiscite in mind. But Goldschmidt soon had to realise that any idea of a cultural union with the German speaking part of the monarchy was absolute anathema to Grundtvig. The latter turned against Goldschmidt, as a dangerous person, - even though he acknowledged the fine literary artist - an international journalist and a Jew, a member of another race with no right to interfere in Danish affairs and with no understanding whatever of Danish popular culture (dansk Folkelighed). In the heat of the fight Grundtvig seems to have forgotten his own defence of the Jews in Denmark during the antisemitic brawl in 1813 and his noble words about the Jews in »Mands Minde«, 1838. Grundtvig does not deny that Goldschmidt has a far deeper insight into European political problems than any other journalist in Danish newspapers. But as a Jew he must resign and keep his mouth shut. Denmark is in mortal danger right now and can only be saved by the indigenous Danes gathering around their own national heritage. Even though Grundtvig’s diatribe against Goldschmidt shows some unpleasant similarities to modern vulgar antisemitism it seems clear that far more essential problems are at stake. Grundtvig’s deep fear of a German rape of Danish culture and his implacable aversion for an academic civilisation excluding the people may have helped to strengthen his feeling of agony on behalf of his country. Goldschmidt was fighting for a dying cause and unhappily got in the way of a Grundtvig who felt that it was »now or never« for his hope for a real Danish renascence. Grundtvig therefore swung Uffe’s heavy sword »Skræp« and Goldschmidt had to give way. Goldschmidt again turned to fiction and eventually became the leading noveist of the 1860s. Years later a Norwegian poet and friend of Goldschmidt’s, A. 0 . Vinje, expressed his admiration for Goldschmidt’s ability to see more than one side of a problem. National identity, he maintained, is a more complex matter than Grundtvig would admit.